Comparative review of liveability indices: trends and insights - Pappu, Meenakshi; Lazar, Nina (Budownictwo i Architektura / Civil and Architectural Engineering, 2025)
The concept of liveability emerged and thrived over two decades, with over thirty global and regional measurable indices developed by various organisations and agencies. All the liveability indices share the overarching goal of analysing urban well-being. There is a significant variation in methodological approach, indicators, weighting percentages, and scope and sampling among the liveability indices. Several studies exist that reviewed and analysed the liveability indices; however, they focus on individual indices in a specific context. This leaves a gap to be acknowledged across the worldwide liveability assessments. Therefore, this research aims to systematically review the existing liveability indices to decode the structural framework. The study is organised into three phases. A detailed review of liveability ranking reports, published literature, and liveability index official websites brought forth a consolidated list of indices. The indices are further grouped based on origin, cluster, methodology, focus domains, sampling, and scope. Further, through a comparative analysis of the structural framework of the indices, the common and specific focus domains were mapped. The findings show that global liveability assessment is dominated by a consultant-driven model, and the core domains aligned with UN SDGs are highlighted as environment, infrastructure, and social equity. The framework must integrate and create context-sensitive assessment and citizen-centric indicators that enable an inclusive assessment to strengthen the quality of life. This research would guide urban planners, policymakers, and researchers in developing transparent and context–sensitive assessment frameworks for urban liveability.